ANALISIS MANAJEMEN KOS KUALITAS LINGKUNGAN UNIT SANITASI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - , Muhammad Maulana; , Bambang Riyanto L.S., Dr., M.B.A. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The main object of this research is to make Total Quality Environmental Management (TQEM) is implemented by Total Quality Management (TQM) in four quality environmental cost category in units of hospital sanitation PKU Muhammadiyah Yogyakarta. The result of research is expected saving of cost without leave to good environmental responsibility. Object of this research is units of hospital sanitation PKU Muhammadiyah Yogyakarta, by identifying the cost of environmental quality in sanitary units. Then make a reclassification of costs in four category cost of environmental quality is, the prevention of environmental cost, appraisal of environmental cost, inernal failure of environmental cost and eksternal failure of environmental cost. After that make the environmental cost quality report separate from the financial statement in sanitary units. And last is make a trend occurred on the application of the environmental over time. On the basic research results, can be seen going cost saving in the implementation cost of environmental quality for the cost of prevention and appraisal of environmental costs, in overall cost saving units of hospital sanitation PKU Muhammadiyah Yogyakarta.